2016
DOI: 10.3846/btp.17.11127
|View full text |Cite
|
Sign up to set email alerts
|

Graduate skills requirements for effective performance in the banking sector

Abstract: This paper aimed to explore the graduate skills requirements in the banking sector. Indepth interviews were carried out with twenty-five managers in ten companies in the banking industry in Turkey. The results show that 40 percent of managers thought universities do not provide their graduates with the skills necessary to be successful in their jobs. Soft skills (i.e. communication, interpersonal relationship, and teamwork skills) are particularly sought after, and managers would also like to see more training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(78 reference statements)
0
5
0
1
Order By: Relevance
“…Bitcoin network is composed of numerous computers linked by the Internet. This network allows to perform the number of sophisticated mathematical procedures that infl uence the demand for Bitcoins in the market and promote the certainty of transfers (Ciaian et al, 2016). With reference to Galdikienė (Duygun Fethi et al, 2006), Bitcoins are gaining their popularity in the countries with high infl ation or strict restrictions of capital movement.…”
Section: Proposed Indicators Of Digital Shadow Economymentioning
confidence: 99%
“…Bitcoin network is composed of numerous computers linked by the Internet. This network allows to perform the number of sophisticated mathematical procedures that infl uence the demand for Bitcoins in the market and promote the certainty of transfers (Ciaian et al, 2016). With reference to Galdikienė (Duygun Fethi et al, 2006), Bitcoins are gaining their popularity in the countries with high infl ation or strict restrictions of capital movement.…”
Section: Proposed Indicators Of Digital Shadow Economymentioning
confidence: 99%
“…According to Cicekli (2016), project management is one of the most advancing fields, as a project manager can work in many fields such as IT, supply chain management, construction management, and banking firms. A study by CIO (2016) found that 37% of the jobs in the professional field require project management skills.…”
Section: Hard and Soft Skills In Pmmentioning
confidence: 99%
“…In particular, the employers wished new accounting hires to demonstrate skills in "asking for clarification or feedback from management….conveying an attitude of respect and interest in clients, and describing situations accurately and precisely to superior(s)" (p. 53) but here also could be found a large discrepancy from skills employers desired and skills new hires demonstrated. Cicekli (2016) studied needed skills of graduates, specifically in banking. The author believed that companies look for graduates with skills, but also look for a new hire's qualities or soft-skills as well.…”
Section: Soft Skills Neededmentioning
confidence: 99%